New Synthetic Method of MgF2 Hollow Nanoparticles by Fluorination of Raw Material Particle Surfaces —Toward Low-temperature Mass Synthesis - Hattori, Shinichi; Tsuji, Ryusuke; Sato, Keisuke; Okada, Yoshiki; Yonezawa, Tetsuo; Kinoshita, Takuya; Omoto, Shin (Funtai Kogakkaishi, 2024)
We conducted research aimed at developing a novel method for synthesis of MgF2 hollow nanoparticles that is simpler than the conventional synthetic method. First, Mg(OH)2 raw material nanoparticles were contact with hydrofluoric acid vapor in a gas-solid reactor at 473 K. As a result, the surfaces of the Mg(OH)2 nanoparticles were fluorinated to obtain Mg(OH)2-MgF2 core-shell particles. Next, the MgF2 hollow nanoparticles were synthesized by soaking the core-shell particles in 1.0 mol/L hydrochloric acid to dissolve only the Mg(OH)2 core portion. We have succeeded in developing a method for synthesizing MgF2 hollow nanoparticles with different MgF2 shell thicknesses by controlling the surface fluorination reaction period of Mg(OH)2 raw material nanoparticles.